Cavitation Selected Issues - Borek, Wojciech; Tański, Tomasz; Król, Mariusz (IntechOpen, 2018)
Cavitation erosion is one of the most popular phenomena of the destruction of engineering materials working in water conditions and various kinds of liquids. The cavitation effect is defined as a physical effect, induced by a variable field of liquid pressures, where bubbles or other voids (caverns) - containing steams of a given liquid, gas, or a steam-gas mixture - are formed, expanded, and disappear. A better understanding of all aspects related to cavitation wear will allow for more thoughtful analysis in the selection of innovative engineering materials additionally protected by various technologies or techniques in the field of surface engineering, and optimization of the design of constructional elements used in the cavitation environment. The novelty of this book is the presentation of extensive knowledge related to cavitation, erosion, and how to protect engineering materials against this phenomenon supported by the results of thorough research by the authors.